EXPECTING THE RETURN OF UIN SUMATERA UTARA'S latHIVa IN THE PREVENTION OF HIV AND AIDS IN NORTH SUMATERA - Achmad Ramadhan (UIN Sumatera Utara Medan, 2020)
As a reflection, when latHIVa was established as a non-structural institution at UIN Sumatera Utara (UiN SU) to tackle HIV and AIDS, the discovery of HIV and AIDS cases at the international level were around 34.3 million people living with HIV, while in 2019 it was estimated that 36.9 million people living with HIV. The cases of HIV and AIDS at the national level in 2000 were 1500 people living with HIV / AIDS (PLWHA) while in 2019 there were 349,882 PLWHA in North Sumatra, and in 2000 there were 30 people living with HIV, while the cases of HIV / AIDS at the level of North Sumatra Province up to August 2019 were 9362 PLWHA. The description of the HIV and AIDS case above describes the epidemic process since the formation of the UIN Sumatera Utara's latHIVa until August 2019. The HIV and AIDS epidemic is like an iceberg phenomenon, which means the numbers of HIV and AIDS cases found above are not the actual numbers. HIV and AIDS do exist. Therefore, WHO (World Health Organization) has formulated that to find out the real numbers, the numbers obtained must be multiplied by 100-200. Thus, if 9362 cases of HIV and AIDS in North Sumatra is multiplied by 100, then there might be 936,200 cases of PLWHA in North Sumatra. Thus, there are around 900 thousand PLWHA who have not been found in North Sumatra.